2022
DOI: 10.28991/esj-2022-06-05-011
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Machine Learning Approach for Waste Bottle Classification

Abstract: The use of machine learning for the image classification process is growing all the time. Many methods can be used to classify an image with good accuracy. Convolutional Neural Network (CNN) and Support Vector Machine (SVM) are popular methods for this case. The two approaches have differences in the data training process to achieve classification objectives. Although there are some differences between these approaches, there are some advantages to both of them. This research explores the comparison of the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Compared with the research results conducted on household subjects, students have about 8 times higher rates of laptop ownership. Specifically, the survey results in 120 households in Can Tho city with 507 people recorded only 60 computers in use, which is only 0.12 units/person [20]. Thereby, it can be seen that the university is the place where a large number of laptops are used, and students are an important contributor to the increase in the number of these devices.…”
Section: Current Status Of Owning a Laptopmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the research results conducted on household subjects, students have about 8 times higher rates of laptop ownership. Specifically, the survey results in 120 households in Can Tho city with 507 people recorded only 60 computers in use, which is only 0.12 units/person [20]. Thereby, it can be seen that the university is the place where a large number of laptops are used, and students are an important contributor to the increase in the number of these devices.…”
Section: Current Status Of Owning a Laptopmentioning
confidence: 99%
“…In addition, only a few related studies have been carried out to estimate the generation of household e-waste in households such as mobile phones, personal computers, televisions, refrigerators, etc. [20][21][22]. The results of these studies show that laptops are not commonly used in households.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Narayanswamy et al [11] explored the optimal multiclass waste classification methods, and compared three image algorithms for waste classification. Fadlil et al [12] studied two methods, namely Convolutional Neural Network and Support Vector Machine, by comparing the training process and the accuracy results of the classification. They found that Convolutional Neural Network is more accurate than Support Vector Machine.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The former aims to locate all instances of transparent containers present in an image, usually involving both identifying the transparent containers and localizing the rectangular boundary surrounding each one. Nevertheless, in spite of vast applications in areas such as service robots [ 9 , 10 ], waste classification [ 11 , 12 ], security checks [ 13 , 14 ] and so on, it provides only very limited information, i.e., no more than presence and localization, about the detected transparent containers. The latter is intended to perceive or estimate the liquid (such as water, alcohol, and other beverages) inside transparent containers by predicting the height of the liquid levels or filled status within the containers.…”
Section: Introductionmentioning
confidence: 99%